2021
DOI: 10.3389/fmicb.2021.631557
|View full text |Cite
|
Sign up to set email alerts
|

Novel Peptides Targeting the β-Clamp Rapidly Kill Planktonic and Biofilm Staphylococcus epidermidis Both in vitro and in vivo

Abstract: Antimicrobial resistance is an increasing threat to global health and challenges the way we treat infections. Peptides containing the PCNA interacting motif APIM (APIM-peptides) were recently shown to bind to the bacterial PCNA homolog, the beta (β)-clamp, and to have both antibacterial and anti-mutagenic activities. In this study we explore the antibacterial effects of these peptides on Staphylococcus epidermidis, a bacterial species commonly found in prosthetic joint infections (PJI). Drug-resistant bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Therefore, MICs for betatide are much lower than doses that affect mammalian cells. APIM-peptides kill bacteria rapidly, i.e., 1× MIC leads to 97% killing within 5 min (Raeder et al, 2021); thus, the short serum half-life of 15-30 min in humans found for the similar anticancer APIMpeptide ATX-101 (Lemech et al, 2021) may therefore be sufficient for good antibacterial in vivo activity. Short serum half-life may rather be an advantage as this lowers the chances of developing immunogenicity and affecting the normal microbiota if given intravenously and/or topically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, MICs for betatide are much lower than doses that affect mammalian cells. APIM-peptides kill bacteria rapidly, i.e., 1× MIC leads to 97% killing within 5 min (Raeder et al, 2021); thus, the short serum half-life of 15-30 min in humans found for the similar anticancer APIMpeptide ATX-101 (Lemech et al, 2021) may therefore be sufficient for good antibacterial in vivo activity. Short serum half-life may rather be an advantage as this lowers the chances of developing immunogenicity and affecting the normal microbiota if given intravenously and/or topically.…”
Section: Discussionmentioning
confidence: 99%
“…Long-time exposure to sub-MIC levels of antibiotics are known to increase TLS and induce resistance development (Kreuzer, 2013;Raeder et al, 2021). To directly examine the resistance development against betatide, we exposed E. coli and S. aureus (both MDR and reference strain) to sub-MIC and 1×-2× MIC levels of betatide through serial passage and measured MIC over 20-30 days.…”
Section: Bacteria Have Low Capacity To Develop Resistance Against Betatidementioning
confidence: 99%
See 1 more Smart Citation
“…The lead antibacterial APIM-peptide, BTP-001 (β-clamp targeting peptide-001), is rapidly bactericidal in several bacterial species, including the ESKAPE pathogens, at doses that do not affect epithelization ( Nepal et al, 2021 ). Biofilm studies demonstrated that BTP-001 eradicates existing biofilms and prevents biofilm formation in Staphylococcus epidermidis , and that it showed promise for use in bone cement to prevent prosthetic joint infection ( Raeder et al, 2021 ). In addition, a recent study showed a strong additive effect of BTP-001 combined with a brominated pyrrolopyrimidine called JK-274 in Staphylococcus aureus ( Olsen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…AMPs are peptides consisting of 5-300 amino acids and are widely distributed in various organisms [6][7][8][9]. In general, AMPs own a broad-spectrum antimicrobial activity [10,11], anti-cancer cell activity [12,13], and antiviral activity [14]. As one of the known AMPs, anti-lipopolysaccharide factors (ALFs) were firstly identified from the hemocytes of Limulus polyphemus [15].…”
Section: Introductionmentioning
confidence: 99%